2017
DOI: 10.1007/s12663-017-0998-7
|View full text |Cite
|
Sign up to set email alerts
|

Associated Injuries in Maxillofacial Trauma: A Study in a Tertiary Hospital in South India

Abstract: Aim Maxillofacial trauma when associated with concomitant injuries has a significant potential for increased morbidity. This study aims to identify the causes of trauma, evaluate the types of associated injuries and to highlight the significance of multi professional collaboration in sequencing of treatment. Patients and Methods A total of 300 patients who reported to the casualty of a tertiary Hospital in Karnataka with facial fractures were enrolled. Results Associated injuries were sustained by 162 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
4
4
0
Order By: Relevance
“…Prior studies conducted in Saudi Arabia also reported similar results attributing motor vehicle accidents as the leading cause of maxillofacial fractures ( Alghamdi et al, 2017 , Ali-Alsuliman et al, 2018 ). The results in our region correspond to international data in Malaysia ( Abosadegh et al, 2017 , Chelvan et al, 2020 ) and South India ( Patil et al, 2018 ). On the contrary, a multicentric European study has found that the primary cause of faciomaxillary fractures is assaults, followed by falls, sports accidents, and road traffic accidents ( Boffano et al, 2015a ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Prior studies conducted in Saudi Arabia also reported similar results attributing motor vehicle accidents as the leading cause of maxillofacial fractures ( Alghamdi et al, 2017 , Ali-Alsuliman et al, 2018 ). The results in our region correspond to international data in Malaysia ( Abosadegh et al, 2017 , Chelvan et al, 2020 ) and South India ( Patil et al, 2018 ). On the contrary, a multicentric European study has found that the primary cause of faciomaxillary fractures is assaults, followed by falls, sports accidents, and road traffic accidents ( Boffano et al, 2015a ).…”
Section: Discussionsupporting
confidence: 91%
“…An analysis of RTAs in SA found that road traffic injuries accounted for 83.4% of all trauma admissions, with the head and neck being the most injured body regions ( Mansuri et al, 2015 ). Injuries to the maxillofacial region are common among RTAs, ranging from minor fractures to severe or gross injuries ( Jose et al, 2016 , Patil et al, 2018 , Singaram et al, 2016 ). Multiple factors affect the incidence and characteristics of maxillofacial fractures, such as sociodemographic, economic, and cultural aspects of the population studied ( Mabrouk et al, 2014 , Singaram et al, 2016 ) Prior studies conducted in Saudi Arabia reported motor vehicle accidents as the leading cause of maxillofacial fractures ( Al-Bokhamseen et al, 2019 , Ali-Alsuliman et al, 2018 , Almasri et al, 2015 , Samman et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They occurred in around 70% of our patients. There is a strong a association between the presence of concomitant injuries and the trauma mechanism [5,24,25]. Head and chest inuries are common in our study.…”
Section: Discussionsupporting
confidence: 57%
“…They occurred in around 70% of our patients. There is a strong association between the presence of concomitant injuries and the trauma mechanism [ 5 , 27 , 28 ]. Head and chest injuries are common in our study.…”
Section: Discussionmentioning
confidence: 99%